THERMAL LOSSES EVALUATION IN 660 MW COAL-FIRED POWER PLANT USING INDIRECT EFFICIENCY METHOD - Muhammad Rizaldi Zaman; Nazaruddin Sinaga (Jurnal Sains dan Teknologi Reaksi, 2021)
Boilers are one of the main equipment in the PLTU apart from turbines and generators. Each year there must be a difference in the actual boiler efficiency value with the conditions during commissioning. Periodically, boiler performance evaluations are carried out in order to identify losses from several factors. In this study, the method used for evaluation is the energy balance method. During the experiment, the standard test guide (ASME PTC - 4) was used. The boiler under test has a capacity of 660 MW. Evaluation is done by comparing the boiler efficiency value at the time of commissioning with the latest performance tests. From the results of performance testing, it is known that the decrease in boiler efficiency when compared with the commissioning results from 86.92% to 82.625%. The reduction in boiler efficiency is due to an increase in heat loss due to dry gas, hydrogen content in coal, and incomplete combustion.Keywords: boiler, efficiency, evaluation, reduction, performance